PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP PENINGKATAN KINERJA PEGAWAI PADA SEKRETARIAT KOMISI PEMILIHAN UMUM DAERAH (KPUD) KABUPATEN SORONG PAPUA BARAT DAYA - Musad, Fadila Bin; Komber, Mervin I.S.; Likewati, Wa Ode (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the influence of motivation and competence on employee performance improvement at the Secretariat of the Regional General Election Commission (KPUD) of Sorong Regency, Southwest Papua. The research employs a quantitative approach using questionnaires distributed to 73 employees. Regression analysis results show that motivation and competence simultaneously have a significant effect on employee performance, with a coefficient of determination of 95.2%. However, partially, only the competence variable has a positive and significant effect, while motivation does not significantly affect employee performance. These findings also indicate that competence is the most dominant factor in improving the performance of KPUD Sorong Regency employees. The limitations of the study lie in the scope of the object and variables studied, suggesting that further research with a broader model and additional variables is necessary for more comprehensive results. This study recommends strengthening employee training and competency development programs as the main priority to support organizational performance improvement.